Correction: Samadi et al. Autism Spectrum Disorder Diagnostic Criteria Changes and Impacts on the Diagnostic Scales-Utility of the 2nd and 3rd Versions of the Gilliam Autism Rating Scale (GARS). Brain Sci. 2022, 12, 537 - Sayyed Ali Samadi; Cemal A. Biçak; Hana Noori; Barez Abdalla; Amir Abdullah; Lizan Ahmed (Brain Sciences, 2023)
In the original publication [...]